Exploring General Practitioner Work in Upper Austria: A Pilot Retrospective Observational Study Across Thirty Practices - ZELKO Erika; PEINBAUER Thomas; VOGGENBERGER Lisa; BEKELAER Fabian; PANTOGLOU Julia; STÜBL Denise; REBHANDL Erwin (Slovenian Journal of Public Health)
This study investigates the differences in patient care across various organisational forms of general practitioners (GPs) in Upper Austria.